Strategic doing: ten skills for agile leadership - Abilkaiyr, A.T. (KAZGUU Liberal Arts Digest Volume 3. M. NARIKBAYEV KAZGUU UNIVERSITY SCHOOL OF LIBERAL ARTS, 2022)
Numerous issues surround people, affecting their businesses, society, as well as the world. Such intricacy, as well as rising networking, are altering the procedure called agile leadership. To drive development and transformation, modern man- agement must fully comprehend the methods of coordinating involved partnerships that traverse organisational barriers. “Strategic Doing: Ten Skills for Agile Leadership” provides a better method for executing decisions inside a fragmentary, non-hierarchical context. The evolution of versatile techniques and organisational linkages is putting pressure on the standard strategic planning approach. A variety of leadership issues were examined. “Strategic Doing: Ten Skills for Agile Leadership” encompasses all 10 skills to direct the learners across numerous cyclical techniques. To deal with the complex challenges pertaining to strategic planning, the writers have devised a new operational technique. This book describes the rapidly changing, transparent, and budget-constrained setting in which many organisations could be positioned. As a result of this review, it was concluded that this work is a useful guide for expanding knowledge in the field of leadership, furthermore, noticeable features of this book are the improvement of previously existing leadership methods and the application of relevant skills.
Keywords: leadership, skills, strategic planning, techniques